GIS three-dimensional modelling with geo-informatics techniques - Bobkowska, Katarzyna; Szulwic, Jakub; Tysiąc, Paweł; Ziółkowski, Patryk (International Conference “Environmental Engineering”, 2017)
The integration issue of virtual models and geo-referenced database have a very broad spectrum of potential applications. Before the integration issue was on the cusp, it was quite problematic to combine three-dimensional models with the geo-referenced database. An integrated database contains a variety of data including such as object orientated data model and raster data. Within this paper, authors present an integration process aiming to make real virtual GIS database which includes the creation of structures, such as bridges, buildings, roads and terrain formations. To create a three-dimensional GIS model high e solution satellite images/point cloud has been used. For 3D modelling and reconstruction purposes, The Blender program has been used since the software provides with quick workflow and user friendly interface. As a result of this study authors concede that integrated techniques for three-dimensional GIS data bases allow conducting easy as well as sophisticated operation in an efficient and non-time consuming way. The subject holds great promise for a future, current challenges focusing on new approaches for conjectures of spatial objects that will be used to boost the capabilities for automatic visualization.
Keywords: discrete-event simulation; GIS; laser scanning; LoD